The proactive personality of state employees - Jassim, Maher Idan; Nafel, Ali Turki (Al-Adab Journal, 2021)
The current research aims to measure the proactive personality of state employees, which means the relatively stable tendency of the individual’s desire to directly influence the effect of a meaningful change in the environment and to identify the differences therein according to the variables of sex, job service. Conducting the outward honesty and validity of the construct and extracting the consistency by performing the method of Fakronbach. The scale was applied to a sample of (400) state employees and their employees. After collecting the information and processing it by appropriate statistical means, the following results were reached: State employees have a highly proactive personality. There is no statistically significant difference in the proactive personality according to the gender and service variable.